This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Given summation is an AGP.
Let S denote the given summation.
S = 3 + 2 . 3 2 + 3 . 3 3 . . . + 1 0 . 3 1 0 3 S = 3 2 + 2 . 3 3 + . . . + 9 . 3 1 0 + 1 0 . 3 1 1 Subtracting these, we get: − 2 S = 3 + 3 2 + . . . + 3 1 0 − 3 1 1 R e d terms are sum of a GP. Calculating it and few manipulations gives: S = 4 1 9 . 3 1 1 + 3 ⇒ S = 8 4 1 4 4 9